Detection technology of multi-magnetic source in spacecraft based on magnetic field gradient tensor. Issue 3 (February 2019) - Xu, Chaoqun; Yi, Zhong; Meng, Lifei; Huang, Kui; Dai, Jialong
Abstract: Multi-magnetic source resolution in spacecraft has been a difficult problem in the field of magnetic survey. Detection technology of magnetic gradient tensor is available to the problem for its high resolution and precision. A spacecraft magnetic source model is established, and a multi-magnetic source model fitting method for spacecraft is presented. The principal invariants of the magnetic field gradient tensor are introduced to ascertain the number and horizontal location of the source, and the Euler equations are combined to complete the multi-magnetic source depth calculation, the best resolution is up to 0.012m, meeting the engineering requirements. The study opens up a new way of multi-magnetic source target detection in spacecraft.